2018
DOI: 10.1111/jcmm.13954
|View full text |Cite
|
Sign up to set email alerts
|

DLG5 suppresses breast cancer stem cell‐like characteristics to restore tamoxifen sensitivity by inhibiting TAZ expression

Abstract: Tamoxifen (TAM) is a primary drug for treatment of estrogen receptor positive breast cancer. However, TAM resistance remains a serious threat to breast cancer patients and may be attributed to increased stemness of breast cancer. Here, we show that discs large homolog 5 (DLG5) expression is down‐regulated in TAM‐resistant breast cancer and cells. DLG5 silencing decreased the sensitivity to TAM and increased the frequency and stemness of CD44+/CD24− breast cancer stem cells (BCSCs) and TAZ, a transducer of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The present study revealed that the upregulation of TAZ was induced by aberrant expression of the cYTOR/miR-125a-5p/SRF axis. It was recently reported that DLG5 inhibited TAZ expression to sensitize breast cancer cells to tamoxifen (38). The results further extended the understandings on how TAZ expression was increased during development of tamoxifen resistance in breast cancer cells.…”
Section: Discussionsupporting
confidence: 62%
“…The present study revealed that the upregulation of TAZ was induced by aberrant expression of the cYTOR/miR-125a-5p/SRF axis. It was recently reported that DLG5 inhibited TAZ expression to sensitize breast cancer cells to tamoxifen (38). The results further extended the understandings on how TAZ expression was increased during development of tamoxifen resistance in breast cancer cells.…”
Section: Discussionsupporting
confidence: 62%
“…Finally, in response to loss of cell polarity, ECM stiffening, focal adhesions and adherens junctions, a number of activated RTKs and GPCRs signal through Rho GTPases and polymerization of filamentous actin to inhibit LATS activity, eventually leading to YAP nuclear translocation. Loss or reduced expression of components of the cell junction-localized cell polarity protein complexes, including the scaffold proteins Scribble (SCRIB) or CRUMBS or of the members of the discs large homolog family (DLG1 or 5), as is frequently observed in cancer, inhibits MST/LATS/YAP interaction, resulting in YAP nuclear translocation, TEAD and SMAD activation and, eventually, the induction of EMT and cancer cell stemness [126,132,133]. In turn, YAP regulates a number of genes involved in upstream RHO/RAC/ROCK signaling [134,135].…”
Section: Yap/taz In Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%
“…Growing evidence suggests that TAZ promotes resistance to various anti‐cancer therapies including cytotoxic chemotherapy (Moroishi et al , ; Zhan et al , ; Liu et al , ). However, our results showed that TAZ knockdown had no inhibitory effect on the clonogenicity of CR and LR cells (Fig A and ).…”
Section: Discussionmentioning
confidence: 99%